An assessment methodology for tunnelling beneath bridges considering soil–structure interaction - Eugene K.L. Wong; Andrea Franza; Peter Hewitt; Giulia M.B. Viggiani (Tunnelling and Underground Space Technology, 2026)

Molecular epidemiology and evolution of norovirus in Australia and New Zealand, 2018 to 2020 - Grace J. H. Yan; Joanne Hewitt; Lewis K. Mercer; Emma F. Harding; Dawn Croucher; Alice G. Russo; Peter G. Huntington; Jason M. Mackenzie; William D. Rawlinson; Peter A. White (Infectious Diseases, 2025)

Advancing ocean monitoring and knowledge for societal benefit: the urgency to expand Argo to OneArgo by 2030 - Virginie Thierry; Hervé Claustre; Orens Pasqueron de Fommervault; Nathalie Zilberman; Kenneth S. Johnson; Brian A. King; Susan E. Wijffels; Udaya T. V. S. Bhaskar; Magdalena Alonso Balmaseda; Mathieu Belbeoch; Marine Bollard; Jacqueline Boutin; et al. (Frontiers in Marine Science, 2025)
The ocean plays an essential role in regulating Earth’s climate, influencing weather conditions, providing sustenance for large populations, moderating anthropogenic climate change, encompassing massive biodiversity, and sustaining the global economy. Human activities are changing the oceans, stressing ocean health, threatening the critical services the ocean provides to society, with significant consequences for human well-being and safety, and economic prosperity. Effective and sustainable monitoring of the physical, biogeochemical state and ecosystem structure of the ocean, to enable climate adaptation, carbon management and sustainable marine resource management is urgently needed. The Argo program, a cornerstone of the Global Ocean Observing System (GOOS), has revolutionized ocean observation by providing real-time, freely accessible global temperature and salinity data of the upper 2,000m of the ocean (Core Argo) using cost-effective simple robotics. For the past 25 years, Argo data have underpinned many ocean, climate and weather forecasting services, playing a fundamental role in safeguarding goods and lives. Argo data have enabled clearer assessments of ocean warming, sea level change and underlying driving processes, as well as scientific breakthroughs while supporting public awareness and education. Building on Argo’s success, OneArgo aims to greatly expand Argo’s capabilities by 2030, expanding to full-ocean depth, collecting biogeochemical parameters, and observing the rapidly changing polar regions. Providing a synergistic subsurface and global extension to several key space-based Earth Observation missions and GOOS components, OneArgo will enable biogeochemical and ecosystem forecasting and new long-term climate predictions for which the deep ocean is a key component. Driving forward a revolution in our understanding of marine ecosystems and the poorly-measured polar and deep oceans, OneArgo will be instrumental to assess sea level change, ocean carbon fluxes, acidification and deoxygenation. Emerging OneArgo applications include new views of ocean mixing, ocean bathymetry and sediment transport, and ecosystem resilience assessment. Implementing OneArgo requires about $100 million annually, a significant increase compared to present Argo funding. OneArgo is a strategic and cost-effective investment which will provide decision-makers, in both government and industry, with the critical knowledge needed to navigate the present and future environmental challenges, and safeguard both the ocean and human wellbeing for generations to come.

Correction: Grouping of chemicals for safety assessment: the importance of toxicokinetic properties of salicylate esters - Abdulkarim Najjar; Sébastien Grégoire; Beate Nicol; Andreas Natsch; Nazanin Golbamaki; Fanny Boisleve; Amaia Irizar; Brian Wall; Angus Swinscoe; Valérie Masini-Etévé; Kaushal Joshi; Anne Marie Api; et al. (Archives of Toxicology, 2025)

Grouping of chemicals for safety assessment: the importance of toxicokinetic properties of salicylate esters - Abdulkarim Najjar; Sébastien Grégoire; Beate Nicol; Andreas Natsch; Nazanin Golbamaki; Fanny Boisleve; Amaia Irizar; Brian Wall; Angus Swinscoe; Valérie Masini-Etévé; Kaushal Joshi; Anne Marie Api; et al. (Archives of Toxicology, 2025)
Grouping of chemicals has been proposed as a strategy to speed up the screening and identification of potential substances of concern among the broad chemical universe under REACH. Such grouping is usually based on shared structural features and should only be used for the prioritization objectives. However, additional considerations (as well as structural similarity) are needed, e.g., mode of action, metabolic pathways, chemical reaction products and physicochemical properties, when regulatory management measures are considered (such as restriction, harmonized classification and labeling). Guidance documents from the European Chemicals Agency (ECHA) recommend considering toxicokinetic information to enhance the robustness of the grouping; however, examples of this approach are lacking. Therefore, this paper shares findings on chemical grouping based on ADME data generated for multiple esters of salicylic acid. These differ with respect to chain length and branching of the alcohol moiety of salicylic acid ester, resulting in a wide range of lipophilicity (LogP 0.21–10.88). Since LogP impacts skin absorption, as well as hydrolysis by carboxylesterases, the bioavailability and thus internal exposure to topically applied salicylate esters can vary considerably. Therefore, we collected skin absorption and metabolism data for 41 salicylates using in vitro testing and in silico models and combined the information to group them according to their potential systemic exposure to the major metabolite, salicylic acid. The results show that, despite a similar general chemical structure, their toxicokinetics vary considerably, indicating the need for better understanding of ADME properties to assess the internal exposure for sound risk assessment.

In vitro to in vivo extrapolation to derive a metabolism factor for estimating the aggregate exposure to salicylic acid after dermal exposure of its esters - Abdulkarim Najjar; Sebastien Grégoire; Beate Nicol; Andreas Natsch; Nazanin Golbamaki; Fanny Boisleve; Amaia Irizar; Brian Wall; Angus Swinscoe; Valérie Masini-Etévé; Dan Selechnik; Anne Marie Api; et al. (Archives of Toxicology, 2024)
As part of the safety assessment of salicylate esters in cosmetics, we developed a metabolism factor based on in vitro to in vivo extrapolation (IVIVE) to provide a better estimation of the aggregate internal exposure to the common metabolite, salicylic acid. Optimal incubation conditions using human liver S9 were identified before measuring salicylic acid formation from 31 substances. Four control substances, not defined as salicylic esters but which could be mistaken as such due to their nomenclature, did not form salicylic acid. For the remaining substances, higher in vitro intrinsic clearance (CL int, in vitro ) values generally correlated with lower LogP values. A “High-Throughput Pharmacokinetic” (HTPK) model was used to extrapolate CL int, in vitro values to human in vivo clearance and half-lives. The latter were used to calculate the percentage of substance metabolised to salicylic acid in 24 h in vivo following human exposure to the ester, i.e. the “metabolism factor”. The IVIVE model correctly reproduced the observed elimination rate of 3 substances using in silico or in vitro input parameters. For other substances, in silico only-based predictions generally resulted in lower metabolism factors than when in vitro values for plasma binding and liver S9 CL int, in vitro were used. Therefore, in vitro data input provides the more conservative metabolism factors compared to those derived using on in silico input. In conclusion, these results indicate that not all substances contribute equally (or at all) to the systemic exposure to salicylic acid. Therefore, we propose a realistic metabolism correction factor by which the potential contribution of salicylate esters to the aggregate consumer exposure to salicylic acid from cosmetic use can be estimated.

Offshore decommissioning horizon scan: Research priorities to support decision-making activities for oil and gas infrastructure - Sarah M. Watson; Dianne L. McLean; Brian J. Balcom; Silvana N.R. Birchenough; Alison M. Brand; Elodie C.M. Camprasse; Jeremy T. Claisse; Joop W.P. Coolen; Tom Cresswell; Bert Fokkema; Susan Gourvenec; Lea-Anne Henry; et al. (Science of The Total Environment, 2023)

Influence of offshore oil and gas structures on seascape ecological connectivity - Dianne L. McLean; Luciana C. Ferreira; Jessica A. Benthuysen; Karen J. Miller; Marie‐Lise Schläppy; Matthew J. Ajemian; Oliver Berry; Silvana N. R. Birchenough; Todd Bond; Fabio Boschetti; Ann S. Bull; Jeremy T. Claisse; et al. (Global Change Biology, 2022)
Offshore platforms, subsea pipelines, wells and related fixed structures supporting the oil and gas (O&G) industry are prevalent in oceans across the globe, with many approaching the end of their operational life and requiring decommissioning. Although structures can possess high ecological diversity and productivity, information on how they interact with broader ecological processes remains unclear. Here, we review the current state of knowledge on the role of O&G infrastructure in maintaining, altering or enhancing ecological connectivity with natural marine habitats. There is a paucity of studies on the subject with only 33 papers specifically targeting connectivity and O&G structures, although other studies provide important related information. Evidence for O&G structures facilitating vertical and horizontal seascape connectivity exists for larvae and mobile adult invertebrates, fish and megafauna; including threatened and commercially important species. The degree to which these structures represent a beneficial or detrimental net impact remains unclear, is complex and ultimately needs more research to determine the extent to which natural connectivity networks are conserved, enhanced or disrupted. We discuss the potential impacts of different decommissioning approaches on seascape connectivity and identify, through expert elicitation, critical knowledge gaps that, if addressed, may further inform decision making for the life cycle of O&G infrastructure, with relevance for other industries (e.g. renewables). The most highly ranked critical knowledge gap was a need to understand how O&G structures modify and influence the movement patterns of mobile species and dispersal stages of sessile marine species. Understanding how different decommissioning options affect species survival and movement was also highly ranked, as was understanding the extent to which O&G structures contribute to extending species distributions by providing rest stops, foraging habitat, and stepping stones. These questions could be addressed with further dedicated studies of animal movement in relation to structures using telemetry, molecular techniques and movement models. Our review and these priority questions provide a roadmap for advancing research needed to support evidence‐based decision making for decommissioning O&G infrastructure.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Tundra Trait Team: A database of plant traits spanning the tundra biome - Anne D. Bjorkman; Isla H. Myers‐Smith; Sarah C. Elmendorf; Signe Normand; Haydn J. D. Thomas; Juha M. Alatalo; Heather Alexander; Alba Anadon‐Rosell; Sandra Angers‐Blondin; Yang Bai; Gaurav Baruah; Mariska te Beest; et al. (Global Ecology and Biogeography, 2018)
Motivation The Tundra Trait Team (TTT) database includes field‐based measurements of key traits related to plant form and function at multiple sites across the tundra biome. This dataset can be used to address theoretical questions about plant strategy and trade‐offs, trait–environment relationships and environmental filtering, and trait variation across spatial scales, to validate satellite data, and to inform Earth system model parameters. Main types of variable contained The database contains 91,970 measurements of 18 plant traits. The most frequently measured traits (> 1,000 observations each) include plant height, leaf area, specific leaf area, leaf fresh and dry mass, leaf dry matter content, leaf nitrogen, carbon and phosphorus content, leaf C:N and N:P, seed mass, and stem specific density. Spatial location and grain Measurements were collected in tundra habitats in both the Northern and Southern Hemispheres, including Arctic sites in Alaska, Canada, Greenland, Fennoscandia and Siberia, alpine sites in the European Alps, Colorado Rockies, Caucasus, Ural Mountains, Pyrenees, Australian Alps, and Central Otago Mountains (New Zealand), and sub‐Antarctic Marion Island. More than 99% of observations are georeferenced. Time period and grain All data were collected between 1964 and 2018. A small number of sites have repeated trait measurements at two or more time periods. Major taxa and level of measurement Trait measurements were made on 978 terrestrial vascular plant species growing in tundra habitats. Most observations are on individuals (86%), while the remainder represent plot or site means or maximums per species. Software format csv file and GitHub repository with data cleaning scripts in R; contribution to TRY plant trait database ( www.try-db.org ) to be included in the next version release.

Linking Ross Sea Coastal Benthic Communities to Environmental Conditions: Documenting Baselines in a Spatially Variable and Changing World - Vonda J. Cummings; Judi E. Hewitt; Simon F. Thrush; Peter M. Marriott; N. Jane Halliday; Alf Norkko (Frontiers in Marine Science, 2018)

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

Polyhydroxybutyrate accumulation by a Serratia sp. - Harriet Lugg; Rachel L. Sammons; Peter M. Marquis; Christopher J. Hewitt; Ping Yong; Marion Paterson-Beedle; Mark D. Redwood; Artemis Stamboulis; Mitra Kashani; Mike Jenkins; Lynne E. Macaskie (Biotechnology Letters, 2008)

Behavioural and pharmacological magnetic resonance imaging assessment of the effects of methylphenidate in a potential new rat model of attention deficit hyperactivity disorder - Katherine N. Hewitt; Yasmene B. Shah; Malcolm J. W. Prior; Peter G. Morris; Chris P. Hollis; Kevin C. F. Fone; Charles A. Marsden (Psychopharmacology, 2005)

Towards a mutant map of the mouse ? new models of neurological, behavioural, deafness, bone, renal and blood disorders - Sohaila Rastan; Tertius Hough; Amy Kierman; Rachel Hardisty; Alexandra Erven; Ian C. Gray; Stepanie Voeling; Adrian Isaacs; Hsun Tsai; Mark Strivens; Rebecca Washbourne; Claire Thornton; et al. (Genetica, 2004)

A study into the anti-microbial properties of an amino functionalised polymer using multi-parameter flow cytometry - Christopher J. Hewitt; Robert Franke; Achim Marx; Beate Kossmann; Peter Ottersbach (Biotechnology Letters, 2004)

Informatics for mutagenesis: the design of Mutabase—a distributed data recording system for animal husbandry, mutagenesis, and phenotypic analysis - Mark A. Strivens; Rachel L. Selley; Simon J. Greenaway; Mazda Hewitt; Xinhong Liu; Kirstin Battershill; Stefan L. McCormack; Karen A. Pickford; Lucie Vizor; Patrick M. Nolan; A. Jacqueline Hunter; Josephine Peters; et al. (Mammalian Genome, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Pneumoconiotic effects of welding-fume particles from mild and stainless steel deposited in the lung of the rat - Roger Hicks; Hua Fan Lam; Kassim J. Al-Shamma; Peter J. Hewitt (Archives of Toxicology, 1984)